2011
DOI: 10.1016/j.ydbio.2011.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Functional dissection of phosphorylation of Disheveled in Drosophila

Abstract: Dishevelled/Dsh proteins (Dvl in mammals) are core components of both Wnt/Wg-signaling pathways: canonical β-catenin signaling and Frizzled (Fz)-planar cell polarity (PCP) signaling. Although Dsh is a key cytoplasmic component of both Wnt/Fz-pathways, regulation of its signaling specificity is not well understood. Dsh is phosphorylated, but the functional significance of its phosphorylation remains unclear. We have systematically investigated the phosphorylation of Dsh by combining mass-spectrometry analyses, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
49
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
3
3

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 51 publications
2
49
1
Order By: Relevance
“…A recent extensive analysis identified dozens of phosphorylated Ser/Thr residues in Dvl (or the Drosophila ortholog, Dsh). However, these modifications were dispensable for ␤-catenin and planar cell polarity signaling in the Drosophila assays (38). The present study and our accompanying report (43) suggest that Dvl2 phosphorylation, particularly at Ser 594 , Thr 595 , and Ser 597 , is relevant for signaling in a Wnt/aPKC pathway.…”
Section: Discussionsupporting
confidence: 50%
“…A recent extensive analysis identified dozens of phosphorylated Ser/Thr residues in Dvl (or the Drosophila ortholog, Dsh). However, these modifications were dispensable for ␤-catenin and planar cell polarity signaling in the Drosophila assays (38). The present study and our accompanying report (43) suggest that Dvl2 phosphorylation, particularly at Ser 594 , Thr 595 , and Ser 597 , is relevant for signaling in a Wnt/aPKC pathway.…”
Section: Discussionsupporting
confidence: 50%
“…Similarly, ITCH ubiquitinates and promotes the degradation of only phosphorylated Dvl, which is different from the alreadyfound E3 ubiquitin ligases for Dvl, such as the KLHL12-Cullin-3 complex, pVHL, NEDL1, and Malin (1,10,26,37), whose ubiquitination of Dvl does not relate to Dvl's phosphorylation state. A previous study reported that Dsh (the Dvl homolog in flies) phosphorylation does not seem to have a major effect on canonical Wnt signaling in Drosophila (43). This may reflect intrinsic differences in the fine regulation of the Wnt signaling pathways between the vertebrate and invertebrate systems.…”
Section: Itch Is a Dvl-binding Proteinmentioning
confidence: 91%
“…3). Dozens of phosphorylation sites have been documented in Dvl proteins, and some have been identified as targets of specific kinases (35)(36)(37)(38). Although phosphorylation sites are widely distributed in the Dvl sequence, they are particularly abundant in the CTD (35).…”
mentioning
confidence: 99%
“…Dozens of phosphorylation sites have been documented in Dvl proteins, and some have been identified as targets of specific kinases (35)(36)(37)(38). Although phosphorylation sites are widely distributed in the Dvl sequence, they are particularly abundant in the CTD (35). Deletion analysis and site-directed mutagenesis have suggested that phosphorylation in this region correlates with formation of psDvl (12,35,39).…”
mentioning
confidence: 99%